The United States and NATO : The Formative Years - Kaplan, Lawrence S. (Book collections on Project MUSE., 1984)
The creation of the North Atlantic Treaty Organization was one of the most important accomplishments of American diplomacy in countering the Soviet threat during the early days of the Cold War. Why and how such a reversal of a 150-year nonalignment policy by the United States was brought about, and how the goals of the treaty became a reality, are questions addressed here by a leading scholar of NATO. The importance of restoring Europe to strength and stability in the post-World War II years was as obvious to America as to its allies, but the means of achieving that goal were far from.